Auditory and visual sensory modalities in the velodrome and the practice of becoming a track cyclist - Themen, K.; Popan, C. (International Review for the Sociology of Sport, 2022)
The aim of this paper is to explore track cycling through visual and aural sensory modalities. We draw on Pink`s work on emplacement and of the researcher serving an apprenticeship by engaging through first-hand experience and learning track practices and routines in which we reflected on our visual and aural senses to account for understanding the body and the transformations it undergoes when riding track. This speaks to Hockey and Allen-Collinson`s call for a `fleshy perspective` by reintroducing the body into sporting practice. Undertaking an auto-ethnographic method, we use diarised notes drawn from six track cycling sessions to account for sensory experiences by reflecting on aural and visual senses in the context of the skills we acquired during track sessions. In this, the emergent narrative situates the body as a place of contestation and transition, whereby our visual and aural modalities are the senses by which we narrate our improving aptitude, and attained physical capital, on the track.